Queer Milton (Early Modern Cultural Studies 1500-1700, 2018)
Queer Milton is the first book-length study dedicated to anti-heteronormative approaches to the poetry and prose of John Milton. Organized into sections on "Eroticism and Form" and "Temporality and Affect," essays in this volume read Milton's works through radical queer interpretive frameworks that have elsewhere animated and enriched Renaissance Studies. Leveraging insights from recent queer work and related fields, contributions demonstrate diverse possible futures for Queer Milton Studies. At the same time, Queer Milton bears witness to the capacity for queer to arbitrate debates that have shaped, and indeed continue to shape, developments in the field of Milton Studies. .